Adaptive fuzzy logic with self-adjusting membership functions based tracking control of surface vessels. (1st June 2022) - Tatlicioglu, Enver; Yilmaz, Bayram Melih; Savran, Aydogan; Alci, Musa
Abstract: Tracking control of surface vessels is aimed where the dynamical model includes uncertainties. In an attempt to design a broadly applicable control methodology, a model independent strategy is pursued. The dynamical uncertainties are modeled via a fuzzy logic network. In the design of the controller, proportional derivative feedback was made use of in conjunction with self-adjusting fuzzy logic compensation term obtained by adaptively updating control representative value matrix along with centers and widths of the membership value vector. Stability of the closed loop system is investigated through novel Lyapunov-based arguments and semi-global practical tracking is guaranteed. Numerical simulation studies are performed that support theoretical findings and demonstrate the effectiveness of the proposed method. Highlights: A novel self-adjusting fuzzy logic based model independent adaptive controller is developed for position tracking control of surface vessels. The closed loop system is proven to remain stable under the proposed control strategy via Lyapunov based analysis tools. The performance of the proposed control strategy is verified via numerical simulations.